The Effects of Screw Length on Stability of Simulated Osteoporotic Distal Radius Fractures Fixed with Volar Locking Plates - Wall, Lindley B. (2012)
PURPOSE: Volar plating for distal radius fractures has caused extensor tendon ruptures secondary to dorsal screw prominence. This study was designed to determine the biomechanical impact of placing unicortical distal locking screws and pegs in an extra-articular fracture model. METHODS: Volar-locking distal radius plates were applied to 30 osteoporotic distal radius models. Radii were divided into 5 groups based on distal locking fixation: bicortical locked screws, 3 lengths of unicortical locked screws (abutting the dorsal cortex [full length], 75% length, and 50% length to dorsal cortex), and unicortical locked pegs. Distal radius osteotomy simulated a dorsally comminuted, extra-articular, fracture. Each constructs stiffness was determined under physiologic loads (axial compression, dorsal bending volar bending) before and after 1000 cycles of axial conditioning and prior to axial loading to failure (2mm of displacement) and subsequent catastrophic failure. RESULTS: Cyclic conditioning did not alter constructs stiffness. Stiffness to volar bending and dorsal bending forces were similar between groups. Final stiffness(N/mm) under axial load was statistically equivalent for all groups: bicortical screws(230), full-length unicortical screws(227), 75% length unicortical screws(226), 50% length unicortical screws(187), unicortical pegs(226). Force(N) at 2 mm displacement was significantly less for 50% length unicortical screws(311) compared to bicortical screws(460), full-length unicortical screws(464), 75% length unicortical screws(400), and unicortical pegs(356). Force(N) to catastrophic fracture was statistically equivalent between groups but mean values for pegs(749) and 50% length unicortical(702) screws were 16-21% less than means for bicortical(892), full-length unicortical(860), and 75% length(894) unicortical constructs. DISCUSSION: Locked unicortical distal screws of at least 75% length produce construct stiffness similar to bicortical fixation. Unicortical distal fixation for extra-articular distal radius fractures should be entertained to avoid extensor tendon injury since it does not appear to compromise initial fixation. CLINICAL RELEVANCE: Biomechanical comparison of distal fixation techniques during volar locked plating for distal radius fracture.